GRAIN YIELD OF TWO BREAD WHEAT Triticum aestivum L. VARAITIES UNDER INFLUENCE OF MAGNETIC TECHNOLOGY - Maha N. Kadum; Husham S. Ali; Naeem. A. Mutlag; Ammar. J. Al-Khazal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field experiment was conducted during the 2011-2012 and 2012-2013 seasons at field of State Agricultural Researchers at Abu Ghraib, in order to study the grain yield of two varieties )Triticum aestivum L.) with magnetized water effect. A randomized complete block design was used with three replications.The main plots included (irrigation with magnetized and irrigation with non-magnetized water), and wheat varieties (Fath and Abu Ghraib3) were distributed on sub plots. The results showed that the plants irrigated with magnetize water were superposed in plant height (97.00 and 94.33) cm, (68.48,70.25) for the number of grains.spike-1, weight of 1000 grains.gm (33.64 and 31.18) and grain yield (5.75,5.63) ton.h-1 for the seasons respectively. In addition, the cultivar of the Fath varieties species superposed in most studied traits, giving the highest number of grains.spike-1 (66.62 and 68.08), weight of 1000 grain.gm (33.81 and 30.97) and grain yield (5.79 and 5.48) ton-1 compared with Abu Ghraib 3 cultivar which gave the lowest mean of the traits, while there were no significant differences Between the two varieties in the number of the spike.m-2 at both seasons respectively. The effect of interaction between cultivars and the addition of magnetized irrigation water was significant in the grain yield characteristics of the cultivars. m -2 (491.0 and 483.00), the number of grains.spike-1 (67.97 and 70.50) and grain yield (6.28 and 5.85) tons. h-1 compared to non-magnetized irrigated plants, which gave the lowest mean for the two seasons respectively.